Bridge to nowhere: A retrospective single-center study on patients using chronic intravenous inotropic support as bridge therapy who do not receive surgical therapy - Rao, Anirudh; Singh, Manavotam; Maini, Mansi; Anderson, Kelley M.; Crowell, Nancy A.; Henderson, Paul R.; Gholami, Sherry S.; Sheikh, Farooq H.; Najjar, Samer S.; Groninger, Hunter (Frontiers in Cardiovascular Medicine, 2022)
Background Many patients with advanced heart failure (HF) are administered chronic intravenous inotropic support (CIIS) as bridge to surgical therapy; some ultimately never receive surgery. We aimed to describe reasons patients “crossover” from CIIS as bridge therapy to palliative therapy, and compare end-of-life outcomes to patients initiated on CIIS as palliative therapy. Methods Single-institution, retrospective cohort study of patients on CIIS as bridge or palliative therapy between 2010 and 2016; data obtained through review of health records and multi-disciplinary selection meeting minutes, was analyzed using descriptive and inferential statistics. Results Of 246 patients discharged on CIIS as bridge therapy, 37 (16%) (male n = 28, 76%; African American n = 22, 60%) ultimately never received surgery. 67 matched patients on CIIS as palliative therapy were included for analysis (male n = 47, 70%; African American n = 47, 70%). The most common reasons for “crossover” from CIIS as bridge therapy to palliative therapy were frailty (n = 10, 27%), cardiac arrest (n = 5, 13.5%), and progressive non-cardiac illnesses (n = 6, 16.2%). A similar percentage of patients in the bridge (n = 28, 76%) and palliative (n = 48, 72%) groups died outside the hospital (P=0.66); however, fewer bridge patients received hospice care compared to the palliative group (35% vs 69%, P < 0.001). Comparing patients who died in the hospital, bridge patients (n = 9; 100%) were more likely to die in the intensive care unit than palliative patients (n = 8; 42%) (P < 0.001). Conclusion Patients on CIIS as bridge therapy who do not ultimately receive surgical therapy “crossover” to palliative intention due to frailty, or development of or identification of serious illnesses. Nevertheless, these “bridge to nowhere” patients are less likely to receive palliative care or hospice and more likely to die in the intensive care unit than patients on CIIS as palliative therapy.